METHODOLOGY FOR DEVELOPING STUDENTS’ RESEARCH SKILLS THROUGH THE EXAMPLE OF THE “RESEARCH METHODOLOGY” COURSE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Orienting students toward scientific research is an integral part of the higher education learning process. In today’s world — marked by an ever-increasing volume of knowledge sources and the widespread use of artificial intelligence — the importance of conducting scientific research remains highly relevant for generating innovative ideas and unique products. This article explores the opportunities for developing students’ research skills within the framework of a learner-centered approach, using the “Research Methodology” course as a case study in higher education.